Neurogenic Thoracic Outlet Syndrome Caused by Vascular Compression of the Brachial Plexus: A Report of Two Cases - Amgad Hanna; Larry O'Neil Bodden; Gabriel R. L. Siebiger (Journal of Brachial Plexus and Peripheral Nerve Injury, 2018)
Thoracic outlet syndrome (TOS) is caused by compression of the brachial plexus and/or subclavian vessels as they pass through the cervicothoracobrachial region, exiting the chest. There are three main types of TOS: neurogenic TOS, arterial TOS, and venous TOS. Neurogenic TOS accounts for approximately 95% of all cases, and it is usually caused by physical trauma (posttraumatic etiology), chronic repetitive motion (functional etiology), or bone or muscle anomalies (congenital etiology). We present two cases in which neurogenic TOS was elicited by vascular compression of the inferior portion of the brachial plexus.